Pro ASP.NET Extensibility - Krause, Jörg (Apress, 2012)
ASP.NET is an established and well-known web application framework, and there are several books on the market with different emphases and at different levels. However, ASP.NET is becoming more and more a foundation technology upon which larger and larger projects are being built. Developers are facing increasing complexity and greater demands to fulfill in their daily tasks. This book examines in-depth the technology beyond the basic ASP.NET topics available elsewhere. It’s full of practical tips and tricks from an experienced developer. You’ll learn not only how things work, but also why. By adopting this knowledge, you will succeed in extending and adapting highly useful functionality in your own projects.$